Effects of training and motivation on auditory P300 brain–computer interface performance. Issue 1 (January 2016) - Baykara, E.; Ruf, C.A.; Fioravanti, C.; Käthner, I.; Simon, N.; Kleih, S.C.; Kübler, A.; Halder, S.
Highlights: Training improves performance with a multi-class auditory P300 speller paradigm. Communication speed after training is one of the highest that has been achieved with auditory brain–computer interface paradigms. Motivation influences BCI performance and P300 amplitude. Abstract: Objectives: Brain–computer interface (BCI) technology aims at helping end-users with severe motor paralysis to communicate with their environment without using the natural output pathways of the brain. For end-users in complete paralysis, loss of gaze control may necessitate non-visual BCI systems. The present study investigated the effect of training on performance with an auditory P300 multi-class speller paradigm. For half of the participants, spatial cues were added to the auditory stimuli to see whether performance can be further optimized. The influence of motivation, mood and workload on performance and P300 component was also examined. Methods: In five sessions, 16 healthy participants were instructed to spell several words by attending to animal sounds representing the rows and columns of a 5 × 5 letter matrix. Results: 81% of the participants achieved an average online accuracy of ⩾70%. From the first to the fifth session information transfer rates increased from 3.72 bits/min to 5.63 bits/min. Motivation significantly influenced P300 amplitude and online ITR. No significant facilitative effect of spatial cues on performance was observed. Conclusions: Training improves performance in an auditory BCI paradigm. Motivation influences performance and P300 amplitude. Significance: The described auditory BCI system may help end-users to communicate independently of gaze control with their environment.